SAYAP PARTAI POLITIK DALAM PELAKSANAAN DEMOKRASI DESA - Annisa Rengganis; Multahibun Multahibun; Sarip Sarip (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2022)
This article is intended to examine the movement of political parties towards the castration of village democracy. Based on two studies conducted before and after the birth of Law Number 6 of 2014 concerning Villages. Marking the economy and the domination of the village elite are clearly illustrated in winning Pilkades. The dominance of clients who are concerned with the services of their parents or siblings who have been approved as village heads. Issues that will be the subject of discussion concern the role of party wings in the process of castration of village democracy. The selection of political parties is not seen in the castration of village democracy. It turns out that the people who control the candidates are those who are involved in political wing organizations. Political organizations have no restrictions as long as they do not prioritize political parties. This situation basically depicts my organization as indirect politics which has castrated village democracy. The organizational movement of the political wing in the village is a problem that is determined by the political parties which include its regulation. The election of village heads in the political process related to the political interests of the people, local politics regulates more influences on the daily life of national politics. The political wing organizations have unwittingly castrated democracy at the village level. Ideally, the village as a laboratory for national democracy should serve as a model and limit the excessive role of politics in achieving democracy nationally.